Depot specific differences in the adipogenic potential of precursors are mediated by collagenous extracellular matrix and Flotillin 2 dependent signaling - Gerald Grandl; Sebastian Müller; Hansjörg Moest; Caroline Moser; Bernd Wollscheid; Christian Wolfrum (Elsevier, 2016)
Objective: Adipose tissue shows a high degree of plasticity, and adipocyte hyperplasia is an important mechanism for adipose tissue expansion. Different adipose depots respond differently to an increased demand for lipid storage. Orchestrating cellular expansion in vivo requires extracellular matrix (ECM) remodeling and a high degree of interaction between cells and ECM. Methods: We studied decellularized primary adipose stromal cell derived ECM of different adipose depots and reseeded them with primary adipose precursors. We tested ECM effect on adipocyte differentiation and analyzed ECM composition using proteomic and immunohistochemical approaches to identify factors in the ECM influencing adipogenesis. Results: We show that the ECM of an adipose depot is the major determinant for the differentiation capacity of primary preadipocytes. Visceral adipose tissue stromal cells differentiate less than subcutaneous cells, which, in turn, are less adipogenic than BAT-derived cells. This effect is based on the ECM composition of the respective depot and not dependent on the precursor origin. Addition of vitamin C pronounces the pro-adipogenic effects of the ECM, indicating the importance of collagenous ECM in mediating the effect. Using a proteomic global and a targeted downstream analysis, we identify Flotillin 2 as a protein enriched in pro-adipogenic ECM, which is involved in orchestrating ECM to preadipocyte signaling. Conclusions: We show that adipose tissue SVF secretes collagenous ECM, which directly modulates terminal differentiation of adipocyte precursors in a depot specific manner. These data demonstrate the importance of the tissue microenvironment in preadipocyte differentiation. Keywords: Adipocyte precursors, Extracellular matrix, Collagen, Stem cell niche, Flotillin 2